Dietary stability in ancient Serbia: Isotopic analysis of two middle bronze age Moriš Cemeteries - Iride Tomažič; Katherine Pompeani; Kara Larson; Amy Nicodemus; John O’Shea; Lidija Milašinović; Alicia Ventresca-Miller (PLoS ONE, 2026)
Food stability refers to a state of consistent and reliable access to key dietary resources and is a crucial factor in the resilience and growth of communities throughout history. The study of human diets has been a focus of archaeological research over recent decades. Isotopic analyses provide unique insight into the breadth and evolution of food consumption, often reflecting broader environmental and social shifts while also indicating human resilience and adaptability to various stressors. Rarely, however, are we able to observe subsistence economies over extended periods within the same archaeologically defined cultural group. This research is the first isotopic project on Bronze Age diet of the Moriš culture (roughly 2700−1500 BCE), and one of the few isotopic studies in the Carpathian Basin. This research presents stable carbon and nitrogen isotopic data from human and animal bone collagen recovered at four Moriš sites. This includes two cemeteries (Mokrin and Ostojićevo) and two settlements (Kiszombor Új Élet and Klárafalva Hajdova), all located within the southern Carpathian Basin. Isotopic analysis of human collagen reveals minimal variation among individuals buried in the cemeteries over the span of 550 years (2100−1550 BCE). Overall, there was food stability during the Early and Late Moriš, with only a slight change in diet towards the end of the Late Moriš period.